Comparison on the effects and safety of tualang honey and tribestaan in sperm parameters, erectile function and hormonal profile among oligospermia males - Ismail, Saiful Bahari; Bakar, Mohd. Bustamanizan; Nik Hussain, Nik Hazlina; Mohd Noor, Nor hayati; Sulaiman, Siti Amrah; Jaafar, Hasnan; Draman, Samsul; Ramli, Roszaman; Wan Yusoff, Wan Zahanim (Hindawi Publishing Corporation, 2014)
This study aims to evaluate the effectiveness of Tualang honey on sperm parameters, erectile function, and hormonal and safety profiles. Methodology. A randomized control trial was done using Tualang honey (20 grams) and Tribestan (750 mg) over a period of 12 weeks. Sperm parameters including sperm concentration, motility, and morphology were analyzed and erectile function was assessed using IIEF-5 questionnaire. Hormonal profiles of testosterone, FSH, and LH were studied. The volunteers were randomized into two groups and the outcomes were analyzed using SPSS version 18. Results. A total of 66 participants were involved. A significant increment of mean sperm concentration , motility and morphology was seen in Tualang honey group. In Tribestan group, a significant increment of mean sperm concentration , and morphology was seen. No significant differences of sperm concentration, motility, and morphology were seen between Tualang honey and Tribestan group and similar results were also seen in erectile function and hormonal profile. All safety profiles were normal and no adverse event was reported. Conclusion. Tualang honey effect among oligospermic males was comparable with Tribestan in improving sperm concentration, motility, and morphology. The usage of Tualang honey was also safe with no reported adverse event.